Polyethylene composite material as well as preparation method and application thereof

By mixing linear low-density polyethylene resin with modified Eucommia rubber and crosslinking agent in a specific proportion and extrusion and granulation, the existing materials are solved in improving strength. While it is difficult to maintain high toughness, it realizes the application requirements of high-strength film materials.

CN119490709APending Publication Date: 2025-02-21WANHUA CHEM GRP CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411822476.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing polyethylene composite materials are difficult to maintain high toughness while increasing their strength, and cannot meet the application needs of high-strength film materials.

Method used

By mixing linear low-density polyethylene resin with modified Eucommia rubber and crosslinking agent in a specific proportion and performing extrusion granulation treatment, a polyethylene composite material with high strength and toughness is formed. Modified Eucommia rubber is modified by unsaturated carboxylic acid, metal oxide and organic peroxide crosslinking agent to generate polyunsaturated carboxylic acid metal salt particles, improving the strength gradient of the material.

Benefits of technology

The balance between high strength and high toughness of polyethylene composite materials is achieved, and is suitable for the application of high strength film materials, avoiding the problem of mutual loss of strength and toughness in traditional modification methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a polyethylene composite material as well as a preparation method and application thereof. The polyethylene composite material is prepared from the following raw material components in parts by weight: 100 parts of linear low-density polyethylene resin, 1-30 parts of modified eucommia ulmoides rubber and 0.02-0.1 part of a cross-linking agent, wherein the modified eucommia ulmoides rubber is obtained by modifying eucommia ulmoides rubber through raw materials including unsaturated carboxylic acid, metal oxide and an organic peroxide cross-linking agent. The polyethylene composite material has good toughness on the premise of having high strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer chemistry and relates to a polyethylene composite material, in particular to a polyethylene composite material and a preparation method and application thereof. Background Art

[0002] Linear polyethylene resin (LLDPE) is formed by copolymerization of ethylene and a small amount of α-olefins. It has a molecular structure with very short comonomer side chains on the main chain of linear ethylene. Due to its relatively regular molecular structure, the material has good transparency, penetration resistance, tear resistance and elongation. It is currently widely used in various packaging bags, garbage bags, industrial bushings, shopping bags and other fields. However, the comonomer will introduce short side chains into the molecular chain of linear polyethylene resin, resulting in a certain degree of decrease in its strength. Therefore, in the field of high-strength film materials, pure linear polyethylene resin does not meet the use requirements.

[0003] Modification of linear low-density polyethylene is an effective method to improve its strength. Commonly used methods include organic / inorganic rigid material filling and compounding, physical / chemical crosslinking, and increasing the crystallization rate and crystallinity. However, physical / chemical crosslinking will lead to excessive crosslinking of linear low-density polyethylene itself, which will lose its original toughness and processing properties while gaining strength, and cannot be used in the film field; the method of filling with organic / inorganic rigid particles requires that the particle size of the rigid particles must be small enough, otherwise collapse and shedding will occur in actual use, and the inorganic material matrix is ​​difficult to be compatible with the filling particles, which basically cannot be effectively used in practical applications; the feasibility of improving material strength by increasing the crystallization rate and crystallinity is relatively high, but increasing the crystallinity will lead to a loss of material toughness.

[0004] In summary, in terms of membrane material applications, existing methods cannot make polyethylene composite materials have both high strength and high toughness. Summary of the invention

[0005] In view of the above defects, the present invention provides a polyethylene composite material, which is made from specific weight portions of raw material components of linear low-density polyethylene resin, modified eucommia rubber and a cross-linking agent, and has higher strength and toughness.

[0006] The present invention also provides a method for preparing the polyethylene composite material. The polyethylene composite material prepared by the method has not only high strength but also high toughness.

[0007] The present invention also provides a membrane material, comprising the polyethylene composite material or the polyethylene composite material prepared by the above preparation method, so the membrane material has both high strength and toughness.

[0008] The present invention provides a polyethylene composite material, wherein the polyethylene composite material is prepared from the following raw material components in parts by weight:

[0009] Based on 100 parts of linear low-density polyethylene resin, 100 parts of linear low-density polyethylene resin, 1 to 30 parts of modified eucommia rubber, and 0.02 to 0.1 parts of vulcanizing agent;

[0010] The modified eucommia rubber is obtained by modifying eucommia rubber with raw materials including unsaturated carboxylic acid, metal oxide and organic peroxide crosslinking agent.

[0011] The polyethylene composite material as described above, wherein the linear low-density polyethylene resin is a copolymer of butene-1 and ethylene, and / or has a molecular weight of 10×10 4 ~13×10 4 g / mol, and / or, a molecular weight distribution index of 3.5 to 5.5, and / or, a melt index at 190°C and 2.16 kg of 0.8 to 2.2 g / 10 min, and / or, an average particle size of 100 to 200 μm.

[0012] The polyethylene composite material as described above, wherein the eucommia rubber comprises at least one of gutta-percha, balata, euonymus gum, and synthetic trans-1,4-polyisoprene;

[0013] And / or, the unsaturated carboxylic acid includes at least one of acrylic acid, crotonic acid, cinnamic acid, and butynedioic acid;

[0014] And / or, the metal oxide includes at least one of zinc oxide, magnesium oxide and aluminum oxide;

[0015] And / or, the organic peroxide cross-linking agent includes at least one of dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, di-tert-butyl peroxide, and di-tert-butylperoxyisopropylbenzene;

[0016] And / or, the vulcanizing agent includes sulfur and / or tetramethylthiuram disulfide.

[0017] The polyethylene composite material as described above, wherein the number average molecular weight of the eucommia rubber is 210,000 to 250,000.

[0018] The polyethylene composite material as described above, wherein the mass ratio of the eucommia rubber, the metal oxide, the unsaturated carboxylic acid and the organic peroxide cross-linking agent is 100:(5-20):(5-20):(0.8-1.5).

[0019] The polyethylene composite material as described above, wherein the raw material components further include at least one of an active agent, an antioxidant, a accelerator, a primary antioxidant, and an auxiliary antioxidant;

[0020] Preferably, based on 100 parts by weight of the linear low-density polyethylene, the active agent is 0.1 to 0.4 parts, and / or the antioxidant is 0.1 to 0.5 parts, and / or the accelerator is 0.05 to 0.2 parts, and / or the primary antioxidant is 0.01 to 0.025 parts, and / or the auxiliary antioxidant is 0.003 to 0.015 parts.

[0021] The polyethylene composite material as described above, wherein the active agent comprises magnesium oxide and / or stearic acid;

[0022] And / or, the antioxidant includes at least one of N-isopropyl-N'-phenyl-p-phenylenediamine, 2,2,4-trimethyl-1,2-dihydroquinoline polymer, 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N-phenyl-α-naphthylamine, N-phenyl-β-naphthylamine, 2,4,6-tris-(N-1,4 dimethylpentyl-p-phenylenediamine)-1,3,5-triazine, and paraffin;

[0023] and / or, the accelerator comprises at least one of N-cyclohexyl-2-benzothiazole sulfenamide, N,N-dicyclohexyl-2-benzothiazole sulfenamide, N-(diethylene oxide)-2-benzothiazole sulfenamide, and N-tert-butyl-2-benzothiazole sulfenamide;

[0024] And / or, the primary antioxidant comprises a hindered phenol primary antioxidant, and the hindered phenol primary antioxidant comprises at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene;

[0025] And / or, the auxiliary antioxidant includes a phosphite auxiliary antioxidant, and the phosphite auxiliary antioxidant includes at least one of tris[2,4-di-tert-butylphenyl]phosphite, tris(nonylphenyl)phosphite and tetrakis(2,4-di-tert-butylphenyl-4-4'-biphenyl)-bisphosphate.

[0026] The present invention also provides a method for preparing the polyethylene composite material described in any one of the above, comprising the following steps:

[0027] 1) performing a first extrusion granulation process on a raw material system including 100 parts by weight of a linear low-density polyethylene resin to obtain first pellets;

[0028] 2) subjecting a raw material system including eucommia rubber, acrylic acid, zinc oxide and an initiator to an in-situ polymerization reaction to obtain modified eucommia rubber; crushing the raw material system including 1 to 30 parts by weight of the modified eucommia rubber to obtain a second pellet;

[0029] 3) performing a second extrusion granulation treatment on a raw material system including the first pellets, the second pellets and 0.02 to 0.1 parts by weight of a vulcanizing agent to obtain a polyethylene composite material.

[0030] The method for preparing the polyethylene composite material as described above, wherein in step 1), the temperature of the first extrusion granulation treatment is 190-220° C., and the rotation speed is 40-70 rpm;

[0031] And / or, in step 3), the temperature of the second extrusion granulation treatment is 190-220° C., and the rotation speed is 40-70 rpm.

[0032] The present invention also provides a membrane material, comprising any one of the polyethylene composite materials described above, or a polyethylene composite material prepared by any one of the preparation methods described above.

[0033] The polyethylene composite material in the present invention is prepared from raw material components including 100 parts by weight of linear low-density polyethylene resin, 1 to 30 parts by weight of modified eucommia rubber and 0.02 to 0.1 parts by weight of a vulcanizing agent, wherein the modified eucommia rubber is obtained by modifying eucommia rubber with raw materials including unsaturated carboxylic acid, metal oxide and organic peroxide crosslinking agent. The three cooperate with each other to make the polyethylene composite material have both high strength and toughness, so as to be applied to high-strength membrane materials. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Linear polyethylene resin (LLDPE) is widely used in various fields due to its good transparency, penetration resistance, tear resistance and elongation, but the short chain branches in its comonomer will lead to a decrease in strength and cannot meet the application requirements of high-strength film materials. At present, the strength of LLDPE is generally improved by modification, but the traditional modification method cannot take into account both strength and toughness, that is, while obtaining high strength, it often loses a certain toughness, resulting in it being unable to be used in the film field.

[0036] The inventors found that although the chemical composition of eucommia rubber is exactly the same as that of natural rubber, its molecular weight configuration is different. Its main component is trans-polyisoprene, and its molecular chain has a high degree of order. At room temperature, the molecular chains can be arranged regularly to form crystals without the need for external stretching, and it gradually shows high elasticity as the degree of cross-linking increases. At the same time, the solubility parameter of eucommia rubber is similar to that of linear polyethylene resin. Both are non-polar materials with good compatibility.

[0037] Based on the above analysis, the inventor mixed eucommia rubber and linear polyethylene resin, and added a crosslinking agent to crosslink the two. Taking advantage of the fact that the degree of crosslinking of eucommia rubber is higher than that of linear low-density polyethylene resin, the eucommia rubber gradually exhibits rubber properties as the degree of crosslinking increases, giving the composite material higher elasticity; and because eucommia rubber has the dual properties of rubber and plastic, it will also retain some plastic state, which can effectively avoid the reduction of the strength of the composite material. At the same time, linear low-density polyethylene resin with a lower degree of crosslinking is conducive to improving the strength of the composite material, avoiding the reduction of other properties such as toughness and transparency due to excessive crosslinking.

[0038] In addition, the eucommia rubber as the rubber phase is dispersed in the linear low-density polyethylene matrix in the form of small particles, which can be used as a reinforcing filler to directly reinforce the linear low-density polyethylene matrix. When the composite material is subjected to external stress, it can serve as a stress concentration point to relieve the external stress.

[0039] The inventors further discovered that the eucommia rubber is modified by using unsaturated carboxylic acids and metal oxides, wherein the unsaturated carboxylic acids and metal oxides generate polyunsaturated carboxylic acid metal salt particles under the action of an organic peroxide crosslinking agent, which are dispersed in the eucommia rubber to obtain modified eucommia rubber. The polyunsaturated carboxylic acid metal salt particles, eucommia rubber and linear low-density polyethylene in the modified eucommia rubber form three strength gradients, which reinforce each other when subjected to external stress, so that the composite material exhibits higher strength.

[0040] Based on the above analysis, the first aspect of the present invention provides a polyethylene composite material, which is prepared from the following raw material components in parts by weight:

[0041] Based on 100 parts of linear low-density polyethylene resin, 100 parts of linear low-density polyethylene resin, 1 to 30 parts of modified eucommia rubber, and 0.02 to 0.1 parts of vulcanizing agent;

[0042] The modified eucommia rubber is obtained by modifying eucommia rubber with raw materials including unsaturated carboxylic acid, metal oxide and organic peroxide crosslinking agent.

[0043] Illustratively, the weight proportion of the modified eucommia rubber in the raw material components is 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts or 30 parts; preferably 5 to 30 parts, more preferably 15 to 30 parts.

[0044] Illustratively, the weight percentage of the vulcanizing agent in the raw material component is 0.02 parts, 0.03 parts, 0.04 parts, 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts or 0.1 parts.

[0045] The polyethylene composite material of the present invention comprises a linear low-density polyethylene resin, a modified eucommia rubber and a crosslinking agent, wherein the modified eucommia rubber is obtained by modifying raw materials comprising unsaturated carboxylic acid and zinc oxide, and the unsaturated carboxylic acid and zinc oxide are in situ polymerized under the action of an organic peroxide crosslinking agent to generate polyunsaturated carboxylic acid metal salt particles, which are dispersed in the eucommia rubber.

[0046] On the one hand, under the action of the cross-linking agent, the molecular chains of the contact surface of eucommia rubber and linear low-density polyethylene resin interpenetrate and entangle with each other, cross-link and form a network structure, which not only makes the material have a higher strength as a whole, but also avoids the occurrence of collapse and shedding during actual use. Due to the different cross-linking degrees of eucommia rubber and linear low-density polyethylene resin, eucommia rubber with rubber-plastic duality gradually shows rubber properties with the increase of cross-linking degree, has high elasticity, and plays a role in absorbing and dispersing stress in the composite material; at the same time, eucommia rubber also maintains a partial plastic state, making it less elastic than ordinary rubber, which can avoid the composite material from reducing its strength due to the rubber phase being too soft. Linear low-density polyethylene resin with a lower degree of cross-linking is conducive to improving the strength of the composite material and avoiding the reduction of other properties such as toughness and transparency due to excessive cross-linking.

[0047] On the other hand, the modified eucommia rubber as the rubber phase is dispersed in the linear low-density polyethylene matrix in the form of small particles, and can be used as a reinforcing filler to directly reinforce the linear low-density polyethylene matrix. When the composite material is subjected to external stress, it can serve as a stress concentration point to relieve the external stress.

[0048] On the other hand, by subjecting eucommia rubber to special modification treatment, the strength and hardness of eucommia rubber can be significantly improved; by mixing modified eucommia rubber with linear low-density polyethylene resin, polyunsaturated carboxylic acid metal salt particles, eucommia rubber and linear low-density polyethylene can form three strength gradients, which reinforce each other when subjected to external stress. In detail, in modified eucommia rubber, polyunsaturated carboxylic acid metal salt particles serve as rigid particle reinforcing fillers of eucommia rubber, which will increase the viscosity of rubber viscous fluid and thus increase the modulus of eucommia rubber; in addition, since polyunsaturated carboxylic acid metal salt particles directly generate reinforcing phases in situ in the eucommia rubber matrix, compared with ordinary fillers directly blended with eucommia rubber, the problem of difficulty in dispersion caused by the interaction between fillers can be effectively avoided, so the modified eucommia rubber in the present invention has strength and hardness superior to ordinary eucommia rubber. In linear low-density polyethylene materials, modified eucommia rubber not only serves as a filler with high strength, high hardness and partial rubber state, but also during the processing, some modified eucommia rubber molecular chains are entangled with linear low-density polyethylene molecular chains. When subjected to external stress, the modified eucommia rubber matrix acts as a stress concentration point to disperse the external stress, thereby improving the strength and toughness of the composite material.

[0049] At the same time, the content of each component needs to be further controlled. Too much modified eucommia rubber will lead to a large proportion of rubber components in the composite material, which will make it difficult for the linear low-density polyethylene matrix to form a continuous phase structure, resulting in a decrease in material strength; and the composite material will exhibit the properties of modified eucommia rubber; too much vulcanizer will lead to an increase in the degree of cross-linking of eucommia rubber and an obvious rubber state, which will lead to a decrease in the strength and hardness of the composite material.

[0050] Therefore, the polyethylene composite material in the present invention has both high strength and toughness, and can meet the application requirements of high-strength membrane materials.

[0051] The "linear low-density polyethylene resin" in the present invention refers to a resin formed by copolymerization of ethylene and α-olefin, having a linear molecular structure and comonomer branches, and a density range of 0.910 to 0.940 g / cm 3 .

[0052] The "modified eucommia rubber" of the present invention can be prepared by the following method:

[0053] The eucommia rubber is plasticized at 70-95°C, unsaturated carboxylic acid and metal oxide are added for mixing, and then an organic peroxide cross-linking agent is added for in-situ polymerization reaction. The reaction time does not exceed 8 minutes. Polyunsaturated carboxylic acid metal salt particles are generated during the reaction and dispersed in the eucommia rubber to obtain modified eucommia rubber.

[0054] The present invention does not specifically limit the types and sources of the linear low-density polyethylene resin, eucommia rubber, unsaturated carboxylic acid, metal oxide, organic peroxide crosslinking agent and vulcanizing agent, and any commercially available product or product prepared by a conventional preparation method known to those skilled in the art may be used.

[0055] Furthermore, the comonomer, molecular weight, molecular weight distribution index, melt index, average particle size and other parameters of the linear low density polyethylene resin can be further controlled to improve the processing performance of the linear low density polyethylene.

[0056] In a specific embodiment, the linear low density polyethylene resin is a butene-1-ethylene copolymer, that is, the α-olefin is butene-1, and the linear low density polyethylene resin is obtained by copolymerizing butene-1 and ethylene.

[0057] In one embodiment, the molecular weight of the linear low density polyethylene resin is 10×10 4 ~13×10 4 g / mol; in detail, the molecular weight is 10×10 4 g / mol, 11×10 4 g / mol, 12×10 4 g / mol or 13×10 4 g / mol.

[0058] In a specific embodiment, the molecular weight distribution index of the linear low density polyethylene resin is 3.5 to 5.5; in detail, the molecular weight distribution index is 3.5, 4.0, 4.5, 5.0 or 5.5.

[0059] In a specific embodiment, the melt index of the linear low density polyethylene resin at 190°C and 2.16kg is 0.8 to 2.2 g / 10min; specifically, the melt index is 0.8 g / 10min, 1.0 g / 10min, 1.2 g / 10min, 1.4 g / 10min, 1.6 g / 10min, 1.8 g / 10min, 2.0 g / 10min or 2.2 g / 10min.

[0060] The "melt index under conditions of 190° C. and 2.16 kg" in the present invention is measured by a melt indexer according to the test standard ASTM D 1238.

[0061] In a specific embodiment, the average particle size of the linear low-density polyethylene resin is 100-200 μm; specifically, the average particle size is 100 μm, 120 μm, 140 μm, 160 μm, 180 μm or 200 μm.

[0062] The "average particle size" in the present invention can be obtained by testing using conventional methods in the art, for example, by testing using a laser particle size analyzer.

[0063] When the comonomer, molecular weight, molecular weight distribution index, melt index or average particle size of the linear low density polyethylene resin meets the above conditions, the linear low density polyethylene has better processing properties.

[0064] Preferably, the linear low density polyethylene resin is 7042 powder and / or 7047 powder. For example, the linear low density polyethylene resin can be 7042 powder; or in one example, the linear low density polyethylene resin can be 7047 powder; or in another example, the linear low density polyethylene resin can be 7042 powder and 7047 powder.

[0065] Furthermore, the types of eucommia rubber, unsaturated carboxylic acid, metal oxide, organic peroxide crosslinking agent and vulcanizing agent also have a certain degree of influence on the strength and toughness of polyethylene composite materials, so it is necessary to screen the above five types of compounds.

[0066] In one embodiment, the unsaturated carboxylic acid includes at least one of acrylic acid, crotonic acid, cinnamic acid, and butynedioic acid;

[0067] The metal oxide includes at least one of zinc oxide, magnesium oxide and aluminum oxide;

[0068] Curing agents include sulfur and / or tetramethylthiuram disulfide;

[0069] The organic peroxide crosslinking agent includes at least one of dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, di-tert-butyl peroxide, and di-tert-butylperoxycumene;

[0070] The eucommia rubber includes at least one of gutta-percha, balata, euonymus gum, and synthetic trans-1,4-polyisoprene.

[0071] When the above five types of compounds are selected from the above compounds respectively, the overall strength and toughness of the polyethylene composite material can be further improved.

[0072] When the above five types of compounds are respectively mixtures of the above multiple specific compounds, the present invention does not specifically limit the ratio between the specific compounds.

[0073] In a specific embodiment, the number average molecular weight of eucommia rubber is 210,000 to 250,000. Within this range, the number average molecular weight of eucommia rubber is relatively suitable, which can achieve a balance between processing performance and mechanical properties, avoid excessive molecular weight resulting in too long molecular chains, and have an adverse effect on processing performance, thereby further improving its reinforcement effect in linear low-density polyethylene resin.

[0074] Exemplarily, the number average molecular weight of eucommia rubber is 210,000, 220,000, 230,000, 240,000 or 250,000; preferably 240,000.

[0075] Furthermore, during the modification process, the ratio of eucommia rubber, metal oxide, unsaturated carboxylic acid and organic peroxide crosslinking agent has a great influence on the comprehensive properties of the modified eucommia rubber.

[0076] Among them, unsaturated carboxylic acid and metal oxide are mainly used as the main reactants to generate polyunsaturated carboxylic acid metal salts. If the unsaturated carboxylic acid is too little, the metal peroxide will not be completely reacted, resulting in insufficient polyunsaturated carboxylic acid metal salts, which will lead to a decrease in the performance of the modified eucommia rubber; if the unsaturated carboxylic acid is too much, the product will have a more obvious acidic odor, affecting its use. Similarly, too little metal oxide will also lead to insufficient polyunsaturated carboxylic acid metal salts; if the metal oxide is too much, the metal oxide will not be completely reacted, and the excess metal oxide will be dispersed in the eucommia rubber as a filler. Although it can play a role in whitening and activation, it will also affect the continuity of the rubber phase and have an adverse effect on the processing and performance of the rubber.

[0077] In a specific embodiment, the mass ratio of eucommia rubber, metal oxide, unsaturated carboxylic acid and organic peroxide crosslinking agent is 100: (5-20): (5-20): (0.8-1.5). Within this range, the modified eucommia rubber has better strength and hardness than the unmodified eucommia rubber, and the processing performance does not change significantly.

[0078] Illustratively, the mass ratio of eucommia rubber, metal oxide, unsaturated carboxylic acid and organic peroxide crosslinking agent is 100:5:5:0.8, 100:20:20:1.5, 100:5:20:1.5, 100:5:5:1.5, 100:20:5:0.8 or 100:20:20:0.8.

[0079] Furthermore, additives may be added to the polyethylene composite material to further improve the comprehensive performance of the composite material. The additives may include activators, antioxidants, accelerators, primary antioxidants, auxiliary antioxidants, and the like.

[0080] Among them, the active agent and accelerator mainly play the role of promoting the vulcanization reaction, improving the physical and mechanical properties of the material and enhancing the processing performance; the role of the antioxidant is mainly to delay the aging process of the material and extend the service life of the material; the role of the main antioxidant is mainly to capture and eliminate free radicals, and the role of the auxiliary antioxidant is to delay or reduce the generation of free radicals. The two work together to inhibit the occurrence of oxidation reactions.

[0081] In a specific embodiment, the raw material components further include at least one of an active agent, an antioxidant, a promoter, a primary antioxidant, and an auxiliary antioxidant;

[0082] Preferably, based on 100 parts by weight of the linear low-density polyethylene, the active agent is 0.1-0.4 parts, the antioxidant is 0.1-0.5 parts, the accelerator is 0.05-0.2 parts, the primary antioxidant is 0.01-0.025 parts, and the auxiliary antioxidant is 0.003-0.015 parts.

[0083] When the raw material components of the polyethylene composite material further include at least one of the above compounds, and the weight percentage of each compound satisfies at least one of the above ranges, the comprehensive performance of the polyethylene composite material can be further improved.

[0084] More preferably, based on 100 parts by weight of the linear low-density polyethylene, the active agent is 0.2-0.4 parts, the antioxidant is 0.1-0.2 parts, the accelerator is 0.08-0.12 parts, the primary antioxidant is 0.012-0.018 parts, and the auxiliary antioxidant is 0.005-0.012 parts.

[0085] Illustratively, the active agent is 0.1 part, 0.15 part, 0.2 part, 0.25 part, 0.3 part, 0.35 part or 0.4 part.

[0086] Illustratively, the antioxidant is 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5 parts.

[0087] Illustratively, the accelerator is 0.05 parts, 0.08 parts, 0.11 parts, 0.14 parts, 0.17 parts or 0.2 parts.

[0088] Illustratively, the primary antioxidant is 0.01 part, 0.012 part, 0.014 part, 0.016 part, 0.018 part, 0.02 part, 0.022 part or 0.025 part.

[0089] Illustratively, the auxiliary antioxidant is 0.003 parts, 0.005 parts, 0.007 parts, 0.009 parts, 0.011 parts, 0.013 parts or 0.015 parts.

[0090] In one embodiment, the active agent comprises magnesium oxide and / or stearic acid;

[0091] The antioxidant includes at least one of N-isopropyl-N'-phenyl-p-phenylenediamine (antioxidant 4010NA), 2,2,4-trimethyl-1,2-dihydroquinoline polymer (antioxidant RD), 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline (antioxidant AW), N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (antioxidant 4020), N-phenyl-α-naphthylamine (antioxidant A), N-phenyl-β-naphthylamine (antioxidant D), 2,4,6-tri-(N-1,4 dimethylpentyl-p-phenylenediamine)-1,3,5-triazine (antioxidant TMPPD), and paraffin;

[0092] The accelerator includes at least one of N-cyclohexyl-2-benzothiazole sulfenamide (accelerator CZ), N,N-dicyclohexyl-2-benzothiazole sulfenamide (accelerator DZ), N-(oxydiethylene)-2-benzothiazole sulfenamide (accelerator NOBS), and N-tert-butyl-2-benzothiazole sulfenamide (accelerator NS);

[0093] The primary antioxidant includes a hindered phenol primary antioxidant, and the hindered phenol primary antioxidant includes at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, and 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene;

[0094] The auxiliary antioxidant includes a phosphite auxiliary antioxidant, and the phosphite auxiliary antioxidant includes at least one of tris[2,4-di-tert-butylphenyl]phosphite, tris(nonylphenyl)phosphite and tetrakis(2,4-di-tert-butylphenyl-4-4'-biphenyl)-bisphosphate.

[0095] When the above five types of compounds are respectively mixtures of the above multiple specific compounds, the present invention does not specifically limit the ratio between the specific compounds.

[0096] The second aspect of the present invention provides a method for preparing the polyethylene composite material of the first aspect, comprising the following steps:

[0097] 1) performing a first extrusion granulation process on a raw material system including 100 parts by weight of a linear low-density polyethylene resin to obtain first pellets;

[0098] 2) subjecting a raw material system including eucommia rubber, acrylic acid, zinc oxide and an initiator to an in-situ polymerization reaction to obtain modified eucommia rubber; crushing the raw material system including 1 to 30 parts by weight of the modified eucommia rubber to obtain a second pellet;

[0099] 3) performing a second extrusion granulation treatment on a raw material system including the first pellets, the second pellets and 0.02 to 0.1 parts by weight of a vulcanizing agent to obtain a polyethylene composite material.

[0100] Specifically, in step 1), a raw material system including a linear low-density polyethylene resin is subjected to a first extrusion granulation treatment to obtain first pellets.

[0101] The present invention does not specifically limit the equipment used for the first extrusion granulation process. For example, a twin-screw extruder can be used.

[0102] The present invention does not specifically limit the temperature and rotation speed in the first extrusion granulation process.

[0103] Furthermore, the raw material system may also include a primary antioxidant and an auxiliary antioxidant.

[0104] In step 2), the eucommia rubber is plasticized, and then unsaturated carboxylic acid and metal oxide are added for mixing, and then organic peroxide crosslinking agent acrylic acid is added for in-situ polymerization to obtain polyunsaturated carboxylic acid metal salt particles, which are dispersed in the eucommia rubber to obtain modified eucommia rubber; the modified eucommia rubber is crushed to obtain a second pellet.

[0105] The present invention does not specifically limit the crushing method. For example, the crushing can be carried out by a rotary pelletizer, freeze crushing, scissor cutting, etc.

[0106] Preferably, the diameter of the second pellet after the crushing process is 0.2 cm to 1 cm. Within this range, the pellet is easier to add to the extruder to prevent the situation of poor feeding. In detail, the diameter of the second pellet can be 0.2 cm, 0.4 cm, 0.6 cm, 0.8 cm or 1 cm.

[0107] Preferably, the mass ratio of eucommia rubber, metal oxide, unsaturated carboxylic acid and organic peroxide crosslinking agent is 100: (5-20): (5-20): (0.8-1.5). Within this range, it is beneficial to improve the strength and hardness of the modified eucommia rubber without affecting its processing performance.

[0108] Furthermore, the raw material system may also include an active agent and an antioxidant.

[0109] In step 3), the raw material system including the first pellets, the second pellets and the vulcanizing agent is uniformly mixed and then subjected to a second extrusion granulation treatment, wherein the mass fraction of the vulcanizing agent is 0.02 to 0.1 parts, to obtain a polyethylene composite material.

[0110] The present invention does not specifically limit the equipment used in the second extrusion granulation process, and the temperature and rotation speed during the process, which may be consistent with the above-mentioned first extrusion granulation process, and will not be described in detail here.

[0111] Furthermore, the raw material system may also include a promoter.

[0112] The preparation method of the polyethylene composite material in the present invention comprises the following steps: mixing and extruding a first pellet comprising a linear low-density polyethylene resin, a second pellet comprising a modified eucommia rubber and a vulcanizing agent, so that the linear low-density polyethylene resin and the modified eucommia rubber are cross-linked under the action of the vulcanizing agent to form a network structure, thereby effectively improving the overall strength of the composite material.

[0113] At the same time, the degree of crosslinking of eucommia rubber is higher than that of linear low-density polyethylene resin. Eucommia rubber with rubber-plastic dual properties partially exhibits rubber properties and partially exhibits plastic properties. While having high elasticity, it can also avoid the reduction in strength of the composite material due to the rubber phase being too soft. Linear low-density polyethylene resin with a lower degree of crosslinking is beneficial to improving the strength of the composite material and can effectively avoid the reduction in toughness due to excessively high degree of crosslinking.

[0114] In addition, the modified eucommia rubber as the rubber phase can play a reinforcing role as a reinforcing filler, so that the composite material can serve as a stress concentration point to relieve the external stress when subjected to external stress, thereby comprehensively improving the strength and toughness of the polyethylene composite material.

[0115] Finally, eucommia rubber was modified with acrylic acid and zinc oxide to generate polyacrylate zinc particles dispersed in eucommia rubber. These particles can form three strength gradients with eucommia rubber and linear low-density polyethylene, which reinforce each other when subjected to external stress, thereby making the composite material present higher strength.

[0116] Therefore, the polyethylene composite material prepared by the above preparation method has both high strength and toughness, and can meet the application of high-strength membrane materials.

[0117] In a specific embodiment, in step 1), the temperature of the first extrusion granulation treatment is 190-220° C., and the rotation speed is 40-70 rpm;

[0118] In step 3), the temperature of the second extrusion granulation treatment is 190-220° C., and the rotation speed is 40-70 rpm.

[0119] When the temperature and rotation speed of the first extrusion granulation process and the second extrusion granulation process are within the aforementioned range, it is beneficial to material processing and molding. If the temperature and rotation speed are too high, the flow rate of the linear low-density polyethylene resin and the polyethylene composite material will be too fast and it will be difficult to pull them into strips.

[0120] Illustratively, the temperature of the first extrusion granulation process is 190°C, 195°C, 200°C, 205°C, 210°C, 215°C or 220°C; and the rotation speed is 40rpm, 45rpm, 50rpm, 55rpm, 60rpm, 65rpm or 70rpm.

[0121] Illustratively, the temperature of the second extrusion granulation process is 190°C, 195°C, 200°C, 205°C, 210°C, 215°C or 220°C; and the rotation speed is 40rpm, 45rpm, 50rpm, 55rpm, 60rpm, 65rpm or 70rpm.

[0122] The third aspect of the present invention provides a membrane material. Since the membrane material comprises the polyethylene composite material of the first aspect or the polyethylene composite material prepared by the preparation method of the second aspect, the membrane material has higher strength and toughness.

[0123] Hereinafter, the polyethylene composite material of the present invention will be described in detail through specific examples.

[0124] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0125] Example 1

[0126] The raw materials of the polyethylene composite material of this embodiment include the following raw material components in parts by weight: 100 parts of linear low-density polyethylene resin, 5 parts of modified gutta-percha, 0.2 parts of active agent stearic acid, 0.1 parts of antioxidant 4010NA, 0.08 parts of accelerator CZ, 0.04 parts of vulcanizing agent sulfur, 0.012 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 0.005 parts of tris[2,4-di-tert-butylphenyl]phosphite;

[0127] Among them, linear low-density polyethylene resin is a copolymer of ethylene and butene-1, with a molecular weight of 10×10 4 g / mol, the molecular weight distribution index is 3.5, the melt index at 190°C and 2.16kg is 1.0g / 10min, and the average particle size is 100μm.

[0128] The preparation method comprises the following steps:

[0129] 1) First, linear low-density polyethylene resin, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris[2,4-di-tert-butylphenyl]phosphite are added to a high-speed mixer according to selected weight proportions and mixed evenly for 15 minutes to obtain a first raw material; then, the first raw material is added to a twin-screw extruder for extrusion granulation, the extruder temperature is 200° C., and the screw speed is 60 rpm to obtain a first pellet;

[0130] 2) Modifying the gutta-percha gum: 100 parts by weight of gutta-percha gum is plasticized at 70°C using a heated two-roll open mill, and after the rubber is rolled, stearic acid and 4010NA are added and mixed; after mixing for 5 minutes, 10 parts by weight of zinc oxide and 10 parts by weight of acrylic acid are added and mixed for 4 minutes; after the acrylic acid, zinc oxide and rubber are evenly mixed in a rubber turning operation, 0.8 parts by weight of DPC is added, and after three triangle rolls, a sheet is produced to obtain a mixed rubber; the mixed rubber is left to stand for more than 24 hours to obtain a modified gutta-percha gum;

[0131] Taking 5 parts by weight of modified gutta-percha gum, crushing the modified gutta-percha gum to obtain second pellets with a diameter of 0.5 cm;

[0132] 3) The first pellet, the second pellet, sulfur and CZ were added into a twin-screw extruder for extrusion granulation. The extruder temperature was 190° C., the screw speed was 70 rpm, and the extrusion time was controlled at 10 min to obtain the polyethylene composite material of this embodiment.

[0133] The preparation methods of the polyethylene composite materials in Examples 2 to 6 are basically the same as those in Example 3, except that the weight fraction of the modified gutta-percha gum is adjusted. The specific adjustments are shown in Table 1.

[0134] The preparation methods of the polyethylene composite materials in Examples 7 to 11 are basically the same as those in Example 3, except that the weight fraction of the vulcanizing agent is adjusted. The specific adjustments are shown in Table 1.

[0135] The preparation methods of the polyethylene composite materials in Examples 12 to 19 are basically the same as those in Example 3, except that the weight fractions of the active agent, antioxidant, accelerator, primary antioxidant and auxiliary antioxidant are adjusted. The specific adjustments are shown in Table 1.

[0136] The preparation method of the polyethylene composite material in Example 20 is basically the same as that in Example 3, except that the weight portion of the active agent is adjusted to 0.5 parts. The specific adjustment is shown in Table 1.

[0137] The preparation method of the polyethylene composite material in Example 21 is basically the same as that in Example 3, except that the weight portion of the antioxidant is adjusted to 0.6 parts. The specific adjustment is shown in Table 1.

[0138] The preparation method of the polyethylene composite material in Example 22 is basically the same as that in Example 3, except that the weight portion of the accelerator is adjusted to 0.5 parts. The specific adjustment is shown in Table 1.

[0139] The preparation method of the polyethylene composite material in Example 23 is basically the same as that in Example 3, except that the weight portion of the primary antioxidant is adjusted to 0.05 parts. The specific adjustment is shown in Table 1.

[0140] The preparation method of the polyethylene composite material in Example 24 is basically the same as that in Example 3, except that the weight portion of the auxiliary antioxidant is adjusted to 0.05 parts. The specific adjustment is shown in Table 1.

[0141] The preparation method of the polyethylene composite material in Example 25 is basically the same as that in Example 3, except that in step 3), the extruder temperature is 230° C. and the screw speed is 90 rpm.

[0142] Comparative Example 1

[0143] The raw materials of the polyethylene composite material of this comparative example include the following raw material components in parts by weight: 100 parts of linear low-density polyethylene resin, 0.012 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 0.005 parts of tris[2,4-di-tert-butylphenyl]phosphite.

[0144] The preparation method comprises the following steps:

[0145] Linear low-density polyethylene resin, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] and tris[2,4-di-tert-butylphenyl] phosphite are taken in selected weight proportions and added to a high-speed mixer and mixed evenly for 15 minutes to obtain a mixture; the mixture is added to a twin-screw extruder for extrusion granulation, the extruder temperature is 200° C., and the screw speed is 60 rpm to obtain the polyethylene composite material of this comparative example.

[0146] Comparative Example 2

[0147] The preparation method of the polyethylene composite material in this comparative example is basically the same as that in Example 1, except that sulfur is not included in the raw material components.

[0148] Comparative Example 3

[0149] The preparation method of the polyethylene composite material in this comparative example is basically the same as that in Example 1, except that the raw material components do not include modified gutta-percha.

[0150] Comparative Example 4

[0151] The preparation method of the polyethylene composite material in this comparative example is basically the same as that in Example 1, except that the weight proportion of the modified gutta-percha in the raw material composition is 35 parts.

[0152] Comparative Example 5

[0153] The preparation method of the polyethylene composite material in this comparative example is basically the same as that in Example 1, except that the weight portion of the vulcanizing agent in the raw material component is 0.2 parts.

[0154] Comparative Example 6

[0155] The preparation method of the polyethylene composite material in this comparative example is basically the same as that in Example 1, except that the gutta-percha gum is not modified.

[0156] The basic parameters are shown in Table 1.

[0157] Table 1

[0158]

[0159] Test example

[0160] 1. Testing the strength and toughness of the polyethylene composite materials prepared in the above examples and comparative examples comprises the following steps:

[0161] The polyethylene composite material prepared above was made into a specimen, and a tensile test was performed according to the method of standard GB / T 1040-92 to obtain the tensile strength.

[0162] The toughness of polyethylene composite materials was tested according to the impact test method of standard GB / T 1043.1-2008 to obtain the simply supported beam notched impact strength.

[0163] The test results are shown in Table 2.

[0164] Table 2

[0165]

[0166] From Table 2, we can see that:

[0167] Compared with the polyethylene composite materials prepared in Comparative Examples 1 to 6, the polyethylene composite materials in Examples 1 to 25 have higher comprehensive properties, wherein the polyethylene composite material in Example 3 has a tensile strength of 27.9 MPa and a simply supported beam notched impact strength of 69.6 kJ / m 2 In the comparative example, the polyethylene composite material of comparative example 4 has a relatively high simply supported beam notched impact strength of 79.3 kJ / m 2, but its tensile strength is only 19.4MPa; similarly, although the polyethylene composite material in Comparative Example 6 has a higher tensile strength of 23.8MPa, its simply supported beam notched impact strength is only 57.7kJ / m 2 .

[0168] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A polyethylene composite material, characterized in that: The polyethylene composite material is prepared from the following raw material components in parts by weight: Based on 100 parts of linear low-density polyethylene resin, 100 parts of linear low-density polyethylene resin, 1 to 30 parts of modified eucommia rubber, and 0.02 to 0.1 parts of vulcanizing agent; The modified eucommia rubber is obtained by modifying eucommia rubber with raw materials including unsaturated carboxylic acid, metal oxide and organic peroxide crosslinking agent.

2. The polyethylene composite material according to claim 1, characterized in that: The linear low-density polyethylene resin is a copolymer of butene-1 and ethylene, and / or has a molecular weight of 10×10 4 ~13×10 4 g / mol, and / or, a molecular weight distribution index of 3.5 to 5.5, and / or, a melt index at 190°C and 2.16 kg of 0.8 to 2.2 g / 10 min, and / or, an average particle size of 100 to 200 μm.

3. The polyethylene composite material according to claim 1 or 2, characterized in that: The eucommia rubber comprises at least one of gutta-percha, balata, euonymus gum, and synthetic trans-1,4-polyisoprene; And / or, the unsaturated carboxylic acid includes at least one of acrylic acid, crotonic acid, cinnamic acid, and butynedioic acid; And / or, the metal oxide includes at least one of zinc oxide, magnesium oxide and aluminum oxide; And / or, the organic peroxide cross-linking agent includes at least one of dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, di-tert-butyl peroxide, and di-tert-butylperoxyisopropylbenzene; And / or, the vulcanizing agent includes sulfur and / or tetramethylthiuram disulfide.

4. The polyethylene composite material according to any one of claims 1 to 3, characterized in that: The number average molecular weight of the eucommia rubber is 210,000 to 250,000.

5. The polyethylene composite material according to any one of claims 1 to 4, characterized in that: The mass ratio of the eucommia rubber, the metal oxide, the unsaturated carboxylic acid and the organic peroxide cross-linking agent is 100: (5-20): (5-20): (0.8-1.5).

6. The polyethylene composite material according to any one of claims 1 to 5, characterized in that: The raw material components also include at least one of an active agent, an antioxidant, a accelerator, a primary antioxidant, and an auxiliary antioxidant; Preferably, based on 100 parts by weight of the linear low-density polyethylene, the active agent is 0.1 to 0.4 parts, and / or the antioxidant is 0.1 to 0.5 parts, and / or the accelerator is 0.05 to 0.2 parts, and / or the primary antioxidant is 0.01 to 0.025 parts, and / or the auxiliary antioxidant is 0.003 to 0.015 parts.

7. The polyethylene composite material according to claim 6, characterized in that: The active agent includes magnesium oxide and / or stearic acid; And / or, the antioxidant includes at least one of N-isopropyl-N'-phenyl-p-phenylenediamine, 2,2,4-trimethyl-1,2-dihydroquinoline polymer, 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N-phenyl-α-naphthylamine, N-phenyl-β-naphthylamine, 2,4,6-tris-(N-1,4 dimethylpentyl-p-phenylenediamine)-1,3,5-triazine, and paraffin; and / or, the accelerator comprises at least one of N-cyclohexyl-2-benzothiazole sulfenamide, N,N-dicyclohexyl-2-benzothiazole sulfenamide, N-(diethylene oxide)-2-benzothiazole sulfenamide, and N-tert-butyl-2-benzothiazole sulfenamide; And / or, the primary antioxidant comprises a hindered phenol primary antioxidant, and the hindered phenol primary antioxidant comprises at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; And / or, the auxiliary antioxidant includes a phosphite auxiliary antioxidant, and the phosphite auxiliary antioxidant includes at least one of tris[2,4-di-tert-butylphenyl]phosphite, tris(nonylphenyl)phosphite and tetrakis(2,4-di-tert-butylphenyl-4-4'-biphenyl)-bisphosphate.

8. A method for preparing the polyethylene composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) performing a first extrusion granulation process on a raw material system including 100 parts by weight of a linear low-density polyethylene resin to obtain first pellets; 2) subjecting a raw material system including eucommia rubber, acrylic acid, zinc oxide and an initiator to an in-situ polymerization reaction to obtain modified eucommia rubber; crushing the raw material system including 1 to 30 parts by weight of the modified eucommia rubber to obtain a second pellet; 3) performing a second extrusion granulation treatment on a raw material system including the first pellets, the second pellets and 0.02 to 0.1 parts by weight of a vulcanizing agent to obtain a polyethylene composite material.

9. The method for preparing the polyethylene composite material according to claim 8, characterized in that: In step 1), the temperature of the first extrusion granulation treatment is 190-220°C and the rotation speed is 40-70 rpm; And / or, in step 3), the temperature of the second extrusion granulation treatment is 190-220° C., and the rotation speed is 40-70 rpm.

10. A membrane material, characterized in that: The polyethylene composite material comprises the polyethylene composite material according to any one of claims 1 to 7, or the polyethylene composite material prepared by the preparation method according to claim 8 or 9.

Citation Information

Patent Citations

  • Preparation method for natural gutta rubber-toughened plastic resin

    CN102827412A

  • Unsaturated carboxylic acid metal salt modified ethylene-propylene-diene monomer (EPDM) and preparation method thereof

    CN103131088A

  • Method of preparing TPV material from eucommia ulmoides and polyolefin thermoplastic resin

    CN105837867A

  • Special cross-linked polyethylene material for rotational molding and preparing process thereof

    CN1524899A

  • Cross-linkable rubber composition for seal material used at oilfield or gas well and seal material

    US20150353811A1